The Role of Tourism Sector in Economic Growth: An Empirical Evidence From Palestine - Tabash, Mosab I. (International Journal of Economics and Financial Issues, 2017)
This study examines the long-term relationship between economic growth and international tourism receipts in the state of Palestine during the period 1995-2014. To achieve the purpose of the study, Gross Domestic Product (GDP) is used as proxy for economic growth while International Tourism Receipts (ITR) is used as a proxy for tourism sector. The findings of the study showed that there is a unique long-term relationship between GDP and international tourism receipts. Furthermore, Granger causality test affirms a causal relationship from international tourism receipts towards economic growth in the state of Palestine. This paper uses an empirical evidence to show the role of tourism sector in economic performance of a country where its economy is highly dependable on foreign aids and donations. So, Palestinian government should develop dynamic policies to promote tourism sector into the country. This in turn leads to generate employment opportunities, poverty alleviation and economic growth. Keywords: Tourism, Palestine, Economic Growth, Co-integration, Causality JEL Classifications: C22, O11, L83